2004
DOI: 10.1007/s00204-003-0521-4
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular studies on cisplatin-induced apoptotic cell death in rat kidney

Abstract: Using morphological and molecular approaches, we characterized cisplatin-induced cell necrosis and apoptosis in rat kidney. Male Sprague-Dawley rats ( n=5 per group) received a single intraperitoneal injection of either cisplatin (5 mg/kg) or saline, and were killed on day 5. Functionally, cisplatin-treated rats developed polyuric acute renal failure. Morphologically, kidneys of cisplatin-treated rats showed overt tubular necrosis associated with apoptosis in the corticomedullary junction. Cell necrosis was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 40 publications
(56 reference statements)
6
53
0
Order By: Relevance
“…Thus regulation of the expression of executioner caspases is crucial prior to the execution of cell death. Several studies including ours have previously demonstrated activation of executioner caspases (caspase-3/7 and -6) in both in vitro 12,13 and in vivo 14,15 models of cisplatin-induced AKI. Similarly, induction of p53 transcription factor was demonstrated in RTECs in both in vitro [16][17][18] and in vivo 19 studies of cisplatin AKI.…”
mentioning
confidence: 63%
“…Thus regulation of the expression of executioner caspases is crucial prior to the execution of cell death. Several studies including ours have previously demonstrated activation of executioner caspases (caspase-3/7 and -6) in both in vitro 12,13 and in vivo 14,15 models of cisplatin-induced AKI. Similarly, induction of p53 transcription factor was demonstrated in RTECs in both in vitro [16][17][18] and in vivo 19 studies of cisplatin AKI.…”
mentioning
confidence: 63%
“…Depending on its concentration, cisplatin induces necrosis as well as apoptosis in these cells, leading to acute renal failure. Multiple signaling pathways are activated by cisplatin in renal tubular cells (Baliga et al, 1998;Megyesi et al, 1998;Shiraishi et al, 2000;Kaushal et al, 2001;Nowak, 2002;Park et al, 2002;Ramesh and Reeves, 2002;Liu and Baliga, 2003;Tsuruya et al, 2003;Arany et al, 2004;Li et al, 2004;Sheikh-Hamad et al, 2004;Yu et al, 2005); however, it is unclear how these signals are integrated to determine cell injury and death (Arany and Safirstein, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In kidneys, cisplatin accumulates in renal tubular cells, resulting in cell injury and death, contributing to the development of AKI (see [1,2] for reviews). Research during the last few years has identified several important signaling pathways that lead to tubular-cell apoptosis during cisplatin nephrotoxicity, including mitogen-activated protein kinase, p53 and others (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%